Ventilation performance and bioenergetics of dekalb white hens in a modern aviary system. (November 2020) - Oliveira, Jofran L.; Ramirez, Brett C.; Xin, Hongwei; Wang, Yu; Hoff, Steven J.
Abstract : The knowledge of bioenergetics and building ventilation rate in intensive livestock housing is important for efficient design and operation of modern animal production facilities. However, information is limited about ventilation performance and house-level heat and moisture production rates of laying hens in contemporary cage-free facilities. Therefore, the objectives of this study were: (i) to determine building ventilation rate (VR) and the associated measurement uncertainty through in-situ calibration of ventilation fans and monitoring of fans runtime in a fully-open aviary laying hen house ( 140, 000 Dekalb White hens); and (ii) to quantify total heat production (THP) of the cage-free hens that is partitioned into house-level latent heat production (LHP) and sensible heat production (SHP) via indirect calorimetry and energy balance methods. THP, SHP, and LHP were expressed for light and dark periods, as well as for time-weighted daily mean, to evaluate the effect of hens' diurnal activities on bioenergetics. VR averaged 4.0 ± 0.4 m 3 h −1 hen −1, ranging from 0.8 to 9.1 m 3 h −1 hen −1 for different seasons. VR uncertainty varied with the operational static pressure (SP) and averaged 9.5% at 10 Pa, 12.7% at 25 Pa, and 17.3% at 40 Pa. Overall, daily mean values were 7.5 ± 0.2 W kg −1 for THP, 4.8 ± 0.3 W kg −1 for SHP, and 2.7 ± 0.2 W kg −1 for LHP. THP decreased by 40% during the dark period (5.1 ± 0.3 W kg −1 ) compared to the light period (8.5 ± 0.3 W kg −1 ).